Influence of certain cognitive and no cognitive variables on achievement in chemistry among secondary school students - Sukanya Rani P (Farook Training College, University of Calicut, 2025)
Achievement in Chemistry at the secondary school level is influenced by a variety of Cognitive and Noncognitive factors. Cognitive variables such as Verbal Intelligence and Scientific Reasoning help students process, analyze, and apply scientific concepts, while Noncognitive variables like Attitude towards Chemistry and Self-efficacy in Chemistry influence motivation and inspiration. Understanding the combined effect of these variables is crucial for enhancing student Achievement in Chemistry. The present study investigates the influence of selected cognitive and Noncognitive variables on Achievement in Chemistry among secondary school students. Cognitive variables considered were Verbal Intelligence and Scientific reasoning, while Noncognitive variables included Attitude towards Chemistry and Self-efficacy in chemistry. Gender, locale and Type of Management of the school were considered as classificatory variables. Achievement in Chemistry was taken as the dependent variable and Cognitive and Noncognitive variables as independent variables. Accordingly, objectives have been framed and hypotheses formulated. survey method was employed and relevant data were collected from a stratified random sample of 1100 students. To measure the variables, standardised tools were used, and the collected data were analysed using descriptive statistics, independent sample t-tests, two-way ANOVA, Pearson's product moment correlation coefficient and multiple regression analysis. The study found significant differences in both Cognitive and Noncognitive variables, as well as Achievement in Chemistry, based on gender, school locale, and type of school management. Female students and government school students scored higher in Verbal Intelligence and Scientific Reasoning, and these key factors are crucial for success in chemistry. However, there was no significant difference between rural and urban students in these cognitive variables, suggesting that locale does not strongly influence them. Female students also showed a more positive Attitude towards chemistry than male students, though both genders had similar levels of Self- efficacy. In terms of Noncognitive factors, locale of the school showed significant differences, and students in government schools had more positive Attitudes towards Chemistry than those in aided schools.The study also revealed that cognitive variables particularly Verbal Intelligence and Scientific Reasoning independently influence Achievement in Chemistry. The study throws light that a positive attitude is strongly correlated with higher achievement in chemistry across all student sub groups. A significant interaction observed among male and rural students, suggest that the combined influence of Attitude and Self-efficacy substantially enhances academic performance. Verbal Intelligence, Scientific Reasoning in Chemistry and Attitude towards Chemistry collectively serve as significant predictors of Achievement in Chemistry. Workshops may be organised for teachers on integrating cognitive skill- building strategies, modules to improve Verbal Intelligence and Scientific Reasoning in boys, such as debate peer tutoring or inquiry-based activities, inclusive classroom environments that promote confidence in boys and girls. Gender - neutral encouragement programmes may be organised in schools, for both boys and girls to perform equally well in chemistry. Science curriculum should incorporate with a cross-disciplinary approach from the school level onwards promoting the integration of language and Science. Curriculum should also include provisions for inquiry based learning, contextualising chemistry concepts within everyday experience and fostering curiosity in the subject.
Keywords: Achievement in Chemistry; Cognitive Variables; Noncognitive variables; Verbal Intelligence; Scientific Reasoning; Attitude towards Chemistry; Self-efficacy in Chemistry; Multiple Regression and Secondary School Students.